National Health Burden of Aspiration Pneumonia on Clinical and Operational Outcomes in Patients With Small Bowel Obstruction Requiring Nasogastric Decompression. Issue 7 (July 2021) - Mehta, Amit; Martin, Tracey; Demiralp, Berna; Steele-Adjognon, Marie; Agarwal, Aishwarya; Mahadev, Srihari; Sharaiha, Reem Z.
Background: Nasogastric tubes (NGTs) are used for decompression in patients with acute small bowel obstruction (SBO); however, their role remains controversial. There is evidence that NGT use is still associated with high incidence of aspiration pneumonia. The aims of this study were to define the prevalence of aspiration pneumonia in patients with SBO managed with an NGT and estimate the association of aspiration pneumonia with 30-day mortality rates, length of stay (LOS), and hospital costs. Materials and Methods: A retrospective cohort study was done using Medicare Inpatient Standard Analytic Files from 2016 to 2018. Patients hospitalized with SBO and managed with NGT were identified using an algorithm of ICD-10-CM codes. The key exposure was aspiration pneumonia. Outcome measures included 30-day mortality rates, LOS, and hospital costs. Results: 53 715 patients hospitalized with SBO and managed with an NGT were identified and included in the analysis. We observed a prevalence of aspiration pneumonia of 7.3%. The 30-day mortality rate was 31% for those who developed aspiration pneumonia vs. 10% for those without pneumonia ( P < .001). Those with aspiration pneumonia, on average, were hospitalized 7.0 days longer ( P < .001) and accrued 20, 543 greater hospitalization costs ( P < .001) than those without pneumonia. Controlling for hospital size and hospital teaching status, we noted a significant association between aspiration pneumonia and increased mortality ( P < .001), longer length of stay ( P < .001), and higher hospital costs ( P < .001). Discussion: Among patients hospitalized for SBO who required an NGT, aspiration pneumonia was associated with a higher mortality rate, longer hospital LOS, and higher total hospital costs. vv